Застосування нейронних мереж до розв’язання задачі тематичного моделювання - Стецун, К. С. (ХНУРЕ, 2024)
This work delves into the application of neural networks, particularly the BAT model, for addressing thematic modeling tasks. Thematic modeling revolves around constructing models that facilitate the organization, understanding, and interpretation of vast collections of textual data. The BAT model (Bidirectional Adversarial Topic model) has garnered attention due to its widespread use in neural networks for text partitioning. This work underscores the potential of neural networks, particularly the BAT model, in advancing thematic modeling techniques and their application across diverse domains.
Keywords: задача тематичного моделювання; нейронна мережа